Formasi Kepribadian Seorang Religius Menuju Kedewasaan Manusiawi - Frans Laka Lazar (Jurnal Pendidikan dan Kebudayaan Missio, 2020)
Everybody expects to become a mature person. The characteristic of mature persons are the ability to know and understand him/herself, to develop his/her pontentialities, to control his/her emotion, and to dealt with conflict and suffering. In order to reach the aim of religious formation, every formation house of religious congregation could develop good formation programs. The result of the study pointed out that some formation houses did not develop yet formation programs fully especially personality formation. The reality speaks to us that there are some religious men or women who are emotional, giving up as facing the difficulties and challenges, and less self-confidence. Therefore, the study could urge formation houses of religious congregation to be serious to develop personality dimension of relirious men or women.